Fundamental Movement Skills Development in Children Aged 5–12: Theory, Evidence, and Pedagogical Models - Khudolii, Mykola; Ivashchenko, Olha; Khudolii, Oleg (Physical Education Theory and Methodology, 2025)
Background. Fundamental movement skills (FMS) represent the foundational basis of children’s motor development and determine their ability to successfully perform more complex sport-specific movements. FMS are strongly associated with physical activity levels, health indicators, sport proficiency, and the long-term trajectory of motor development. At the same time, substantial heterogeneity exists in definitions, pedagogical approaches, and assessment criteria, which complicates the standardization of training programs. Objectives. To summarize contemporary theoretical, empirical, and pedagogical approaches to the development of fundamental movement skills in children aged 5–12 and to systematize evidence-based models of instruction in physical education and early sport training. Materials and Methods. Literature searches were conducted in Scopus, Web of Science, PubMed, ERIC, and Google Scholar (2000–2025). Search terms included: “fundamental movement skills,” “motor learning,” “physical education,” “instructional model,” “manipulative skills,” “early sport training.” Additional snowball searches were carried out using the reference lists of key publications by Barnett, Ivashchenko, Khudolii, and Marchenko. Included sources comprised empirical studies, reviews, conceptual models, and programmatic reports; excluded were clinical samples and studies not reporting FMS-related data. Evidence synthesis was conducted by thematic domains. Results. Four major research directions were identified: (1) Theoretical foundations of FMS: three categories of skills (locomotor, manipulative, stability), their coordinative basis, and contextual dependence on instructional conditions. (2) Associations between FMS, physical activity, and health: higher FMS levels are linked to increased physical activity, better fitness, and reduced obesity risk; manipulative skills are the strongest predictor of sport participation. (3) Pedagogical models of instruction: game-based interventions (GEL approach), sensory-integrative methods, structured repetition modes, and programmed instruction of complex actions demonstrate the highest effectiveness. (4) Manipulative and complex motor actions: development of throwing, catching, striking, and dribbling skills is essential for children’s involvement in sports; optimized training loads (6 repetitions, 45–60 s rest) ensure maximal learning gains. Conclusions. Development of FMS at ages 5–12 is a key component of physical education and early sport training. The most effective approaches combine game-based contexts, multisensory stimulation, and structured repetition modes. There is an urgent need to standardize FMS assessment criteria, unify testing instruments, and integrate modern digital movement-analysis tools.